Investigation of Bank Liquidity of Macroeconomic and Bank-Specific Determinants – A Panel Data Approach - Kasana, Ekta; Chauhan, Kshamta; Sahoo, Bibhu Prasad (The Economics and Finance Letters, 2022)
Liquidity is critically significant for the banks and banking system components. This study investigates the macroeconomic determinants along with bank-specific determinants of Indian banks. This study considered 50 banks for analysis from 2008 onwards. The result was drawn by employing the generalized method of moments. More precisely, the findings of this study indicate that liquid assets to total assets revealed a substantial relationship with bank determinants of deposits, capital, bank size, and net interest margin. The liquid assets to total assets was also found to have a significant association with macroeconomic determinants of interest rate, weighted average call rate, and gross domestic product. In the case of loans to total assets, bank-specific variables of asset management and net interest margin have a significant relationship, while for macroeconomic variables, only the interest rate has a significant association with bank liquidity. The other independent variables such as cash reserve ratio, return on assets, and non-interest income have an insignificant influence on the liquidity ratios. The findings are significant for bankers, regulators, analysts, and policymakers in managing bank liquidity. The current study is useful for other economies with a similar economic framework to India to improve their bank liquidity structure.